COHERENCE OF MULTICULTURAL LIFE OF THE TANON PEOPLE, PAPAR DISTRICT, KEDIRI REGENCY : KOHERENSI KEHIDUPAN MULTIKULTURAL DI MASYARAKAT DESA TANON KEC. PAPAR KAB. KEDIRI - Arif, Mohammad; Darwati, Yuli (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
This study uses qualitative research methods with the type of research "grounded research". Data mining through independent interviews is a sharp realization and at the same time presents a way out of theoretical stagnation in the social sciences, producing descriptive data in the form of written or spoken words of people and observable behavior. This approach is directed at the location and individuals in a holistic (whole) inductive manner in Tanon Village, Papar District, Kab. Kediri. The results of this research data indicate that the religious life of the people of Tanon Village, Papar District, Kediri Regency is full of tolerance, lives in harmony, is safe and peaceful. This life is seen in activities such as death, marriage, all people help each other even though their religion is different. Harmony and tolerance can also be seen in Eid, Nyepi and Christmas activities in Tanon village. They visit each other. Several events were held to enliven the holiday, such as an open house at the Village Hall, which was attended by people of different religions. The Takbir Keliling Festival was held by involving committees from Hindu youth, as well as the ogoh-ogoh parade which also involved committees from Muslim youth and Banser, as well as all existing multi-religious elements.